The Urgency of Developing an Interactive Learning Model - Ramadhanul Ikhsan; Cisia Padila; Dedek Saputra; Sasmi Nelwati; Ahmad Sabri (Al-Fadlan: Journal of Islamic Education and Teaching, 2024)
This study discusses the urgency of developing an interactive learning model in improving student achievement and motivation in Islamic religious education subjects, this study is considered important because it is closely related to the progress of Islamic religious education in Indonesia. This study will reveal the importance of developing a learning model in improving student achievement and motivation in Islamic religious education subjects. The approach used in this study is a qualitative research method with a focus on descriptive analysis of various written texts. The qualitative method was chosen because this study emphasizes more on literature and library studies. Researchers read, understand, and analyze written sources that are relevant to the problems being studied. Data were collected through searches from various sources such as theses, dissertations, scientific articles, and e-books accessed through electronic media and the internet. From the results of the study, it can be seen that there are several factors that influence the improvement of student achievement and motivation, including: family factors, teacher factors, student factors, facilities and infrastructure factors. This study is expected to be a reference in improving Islamic religious education in Indonesia.